Aspects of society and economy of Bihar - Sinha, Ranjan (New Delhi, India : Commonwealth Publishers, 1989)
With reference to Patna.
Spine title: Aspects of society & economy of Bihar, 1765-1856.
Includes index.
Bibliography: p. [191]-206.
Keywords: Patna (India) -- Economic conditions; Patna (India) -- Social conditions